2020
DOI: 10.1111/1749-4877.12476
|View full text |Cite
|
Sign up to set email alerts
|

Personality and behavioral changes in Asian elephants (Elephas maximus) following the death of herd members

Abstract: Elephants are highly social beings with complex individual personalities. We know that elephants have a general interest in death, investigating carcasses, not just limited to kin; however, research does not explore in depth whether individuals change their behavior or personality following traumatic events, such as the death of a conspecific. Within a captive herd of Asian elephants (Elephas maximus) housed at Chester Zoo, UK, we measured social behavior and proximity and personality using the Ten‐Item Person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…The deaths of calves can significantly alter the behaviour and personality of surviving herd members [ 31 ]. Therefore, another important question is whether dead calf carrying is mediated by the carrier's altered physiological state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deaths of calves can significantly alter the behaviour and personality of surviving herd members [ 31 ]. Therefore, another important question is whether dead calf carrying is mediated by the carrier's altered physiological state.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to African savanna elephants, Asian elephants live in relatively small groups with weaker and nonlinear dominance networks among social units [ 30 ], and associations between females that tend to be temporally stable across seasons and years [ 29 ]. The importance of interactions among individuals and herds in elephant societies raises the issue of survivors' psychological responses triggered by the death of a group member [ 31 ]. However, Asian elephants remain largely unstudied in terms of thanatological behaviours, especially under free-ranging conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a further comparison concerning 'visiting the carcass' cannot be made between Asian and African elephants. In natural setting, elephants have been reported to visit the burial site at various stages of decomposition both in Africa (Hawley et al 2016;Goldenberg and Wittemyer 2019;Rutherford and Murray 2020) and Asia (Pokharel and Sharma 2022). This case study shows the opposite behaviour altogether.…”
Section: Postmortem Behaviourmentioning
confidence: 67%
“…We deem it urgent as the herd's behaviour (especially the mother) would vary in deaths due to natural illness and accidents (injury and wounding). Calves up to five years of age experience mortality risks due to various factors such as maternal age, sex of the calf, inter-birth intervals, and whether firstborn or later-born (Mar et al 2012;Rutherford and Murray 2020). Controlled studies have reported 43.3% of deaths due to accidents among young calves (Mar et al 2012), and therefore, the resultant behaviour remains critical and dependent on the cause of death.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental variations can impose pressures on an animal’s physiology [ 1 , 2 , 3 ], phenology [ 4 , 5 , 6 ], morphology [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], distribution [ 20 ], and life-history strategies [ 21 , 22 , 23 , 24 , 25 , 26 ]. The ecogeographic patterns of covariation between biological traits and environmental variables [ 27 ] provide opportunities to assess the adaptions of animals in response to the selection pressures imposed by significant variations in temperature, precipitation, and associated microclimate variations [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%